Positive electrode material, electrochemical device, and electronic device
By doping elements in the positive electrode material of lithium-ion batteries to regulate oxygen defects and lithium-oxygen layer spacing, combined with sulfur-containing double bond compounds or polynitrile compounds, the oxygen release and structural stability problems of lithium-ion batteries at high voltage are solved, and the The amount of delitting and energy density are improved, and the electrochemical performance is improved.
Patent Information
- Application Number
- CN202380038398.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-10-20
AI Technical Summary
Under high voltage and high deliques of lithium-ion batteries, the surface oxygen release and structural phase change of the positive electrode material lead to problems such as cell circulation diving and gas production, and the high content of nickel and cobalt limits the energy density and kinetic properties of the material. .
By doping elements in the lithium layer to regulate oxygen defects and lithium oxygen layer spacing, activate the redox nature of transition metals, reduce oxygen activity, inhibit oxygen release and structural collapse, lithium transition metal composite oxides and sulfur-containing oxygen double bond compounds are used. Or polynitrile compounds improve electrochemical properties.
It significantly improves the deliquency and energy density of the positive electrode material, improves the structural stability and floating charging performance at high temperatures and high voltages, and extends the working life of the battery.
Smart Images

Figure CN119156718A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to a positive electrode material, an electrochemical device and an electronic device. Background Art
[0002] With the popularity of consumer electronic products such as laptops, mobile phones, tablets, mobile power supplies and drones, the requirements for batteries are becoming more and more stringent. For example, batteries are not only required to be lightweight, but also to have high capacity and long service life. Lithium-ion batteries have become mainstream in the market with their outstanding advantages such as high energy density, high safety, no memory effect and long service life.
[0003] In pursuit of higher energy density, lithium-ion batteries have been developing in the direction of increasing voltage and increasing lithium removal. Under high voltage and high lithium removal, the problems of oxygen release and structural phase change on the surface of the positive electrode material are also fully exposed, leading to problems such as battery cycle diving and gas production. Therefore, it is urgent to develop a positive electrode material with high lithium removal and high stability under high voltage. Summary of the invention
[0004] In view of this, in a first aspect, the present application provides a positive electrode material, wherein an electrode comprising the positive electrode material is assembled with a lithium sheet into a button battery, and when the button battery is charged to 4.4V, the lithium desorption amount of the positive electrode material is above 80%.
[0005] Normally, the positive electrode ternary material mainly generates capacity through the valence change of two elements, nickel and cobalt. The capacity of the positive electrode material is related to the nickel content contained in the positive electrode material. The higher the nickel content, the higher the capacity of the positive electrode material. The Mn in the positive electrode material is in the +4 valence state, which does not provide capacity and further limits the energy density of the material. At the same time, the low electrochemical activity of manganese leads to poor kinetics of the material. Under deep delithiation, the oxygen ion activity on the surface of the material is high and it is easy to have side reactions with the electrolyte, resulting in increased interfacial impedance or gas production. In addition, when the distance between the lithium oxygen layers in the ternary material is low, it will hinder the diffusion of lithium ions at the end of charging, resulting in low battery capacity.
[0006] The inventors of the present application have discovered that element doping in the lithium layer by synthetic means can regulate the internal oxygen defects and the distance between the lithium oxygen layers. The introduction of oxygen defects inside the material can activate the redox properties of the transition metal and greatly improve the energy density of the material. At the same time, doping the lithium layer with elements of high ionic radius increases the distance between the lithium oxygen layers, which can promote the full deintercalation of lithium ions, thereby greatly increasing the amount of lithium removed from the positive electrode material. In addition, the oxygen vacancies formed on the surface can reduce the activity of oxygen on the surface of the material, stabilize the outer oxygen ions of the material, and inhibit the release of oxygen and gas production of the positive electrode material during floating charge and high-temperature storage, thereby improving the floating charge performance and high-temperature storage performance of the electrochemical device.
[0007] According to some embodiments of the present application, when the button cell is charged to 4.4V, the cathode material has a strongest oxygen release peak above 250°C in the range of 100°C to 500°C in the TG-MS test. The oxygen vacancies formed inside and on the surface of the cathode material of the present application reduce the activity of oxygen in the material, and the element doping in the lithium layer inhibits the structural collapse of the material under high lithium removal state, thereby inhibiting the oxygen release of the cathode material and improving the structural stability of the cathode material under high temperature and high voltage.
[0008] According to some embodiments of the present application, when the button battery is charged to 4.4V, based on the mass of 50mg of the positive electrode material, the oxygen ion flux intensity of the positive electrode material in the TG-MS test is IA / 50mg, and the temperature is T℃, wherein in the range of 100℃ to 500℃, the differential dI / dT of I relative to T is less than or equal to 3×10 -13 The cathode material of the present application can inhibit the drastic oxygen release of the material, thereby improving the structural stability of the cathode material under high temperature and high voltage.
[0009] According to some embodiments of the present application, when the button cell is charged to 4.4V, based on the mass of 50mg of the positive electrode material, the heat released by the positive electrode material in the TG-DSC test is W mW / 50mg, and the temperature is T°C, wherein, in the range of 100°C to 500°C, the differential dW / dT of W relative to T is less than or equal to 0.01. The positive electrode material of the present application can suppress the violent oxygen release and heat release of the material, and improve the structural stability of the positive electrode material at high temperature and high voltage.
[0010] According to some embodiments of the present application, an electrode including the positive electrode material is assembled into a button battery with a lithium sheet. When the button battery is charged and discharged with a current of 0.1C in a voltage range of 3.0V to 4.4V, the obtained capacity-voltage differential dQ / dV curve has a first oxidation peak and a first reduction peak in the range of 4.2V to 4.4V.
[0011] According to some embodiments of the present application, the peak voltage of the first oxidation peak is Vo1, the peak voltage of the first reduction peak is Vr1, and |Vol-Vr1|≤0.3V.
[0012] According to some embodiments of the present application, the capacity-voltage differential dQ / dV curve has a second oxidation peak and a second reduction peak in the range of 3.6V to 4.0V, the peak voltage of the second oxidation peak is Vo2, the peak voltage of the second reduction peak is Vr2, and |Vo2-Vr2|≤0.3V.
[0013] According to some embodiments of the present application, the positive electrode material includes a lithium transition metal composite oxide, which includes element T and an optional element Q, wherein the element T includes at least one of Ni, Co or Mn, and the element Q includes at least one of K, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge.
[0014] In some embodiments, the molar percentage of Ni is 30% to 70% based on the total molar amount of the element T. In some embodiments, the molar percentage of Mn is 0% to 70% based on the total molar amount of the element T. In some embodiments, the molar percentage of Co is 0% to 50% based on the total molar amount of the element T.
[0015] According to some embodiments of the present application, the lithium transition metal composite oxide further includes a Na element, and based on the total molar amount of the element T and the element Q, the molar percentage of the Na element is 0.1% to 20%.
[0016] According to some embodiments of the present application, based on the total molar amount of the element T and the element Q, the molar percentage of the element T is 90% to 100%, and the molar percentage of the element Q is 0% to 10%.
[0017] According to some embodiments of the present application, the lithium transition metal composite oxide further includes element R, and the element R includes at least one of F, Cl, Br, I or N. Based on the total molar amount of the element T and the element Q, the molar percentage of the element R is 0.1% to 10%.
[0018] According to some embodiments of the present application, in the lithium transition metal composite oxide, the ratio of the molar amount of the Li element to the total molar amount of the element T and the element Q is 0.5 to 1.1.
[0019] According to some embodiments of the present application, the lithium transition metal composite oxide has a layered crystal structure.
[0020] According to some embodiments of the present application, the lithium transition metal composite oxide includes Li x1 Na x2 Ni y1 Mn y2 Co y3 Q z1 O 2±m R m, 0.5≤x1≤1.1, 0.001≤x2≤0.2, 0.3≤y1≤0.7, 0≤y2≤0.7, 0≤y3≤0.5, 0≤z1≤0.1, 0≤m≤0.1, wherein the element R includes at least one of F, Cl, Br, I or N.
[0021] In a second aspect, the present application further provides an electrochemical device, the electrochemical device comprising a positive electrode plate, the positive electrode plate comprising the positive electrode material according to the first aspect of the present application.
[0022] In some embodiments, the electrochemical device further comprises an electrolyte, wherein the electrolyte comprises an additive, and the additive comprises at least one of a sulfur-oxygen double bond compound or a polynitrile compound. The sulfur-oxygen double bond compound can form an oxidation-resistant protective film on the surface of the positive electrode material, and the rich S element can stabilize the high-valent transition metal in the charged state, thereby better inhibiting the release of oxygen on the surface of the positive electrode material and the oxidative decomposition of the electrolyte. The polynitrile compound can complex with the transition metal on the surface of the positive electrode active material, stabilize the transition metals such as nickel, cobalt, and manganese on the surface of the positive electrode material, inhibit the release of oxygen on the surface of the positive electrode material, and thus improve the structural stability of the positive electrode material at high temperature and high voltage.
[0023] According to some embodiments of the present application, the sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone, vinyl sulfate, 2,4-butane sultone, 1,4-butane sultone, methylene disulfonate, 1,3-propane disulfonic anhydride, 4-methylethylene sulfate or pentaerythritol bicyclic sulfate.
[0024] According to some embodiments of the present application, based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond-containing compound is 0.1% to 5%.
[0025] According to some embodiments of the present application, the polynitrile compound includes at least one of succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, methyl glutaronitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3,5-pentanetricarbonitrile, 1,3,6-hexanetrinitrile or 1,2,3-tris(2-cyanoethoxy)propane.
[0026] According to some embodiments of the present application, based on the mass of the electrolyte, the mass percentage of the polynitrile compound is 1% to 10%.
[0027] In a third aspect, the present application provides an electronic device, which includes the electrochemical device described in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1The oxygen ion flux intensity curves obtained by TG-MS testing of Comparative Example 2 and Example 21 are shown.
[0029] Figure 2 The differential curves of oxygen ion flux intensity and temperature obtained by TG-MS test of Comparative Example 2 and Example 1 are shown.
[0030] Figure 3 The first charge and discharge curves of Comparative Examples 1 and 2 and Example 15 are shown.
[0031] Figure 4 The capacity-voltage differential dQ / dV curves of Comparative Examples 1, 2 and Example 15 are shown. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0033] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0034] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0035] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0036] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0037] 1. Cathode Materials
[0038] In a first aspect, the present application provides a positive electrode material, wherein an electrode comprising the positive electrode material and a lithium sheet are assembled into a button battery. When the button battery is charged to 4.4V, the amount of lithium removed from the positive electrode material is above 80%, for example, it can be 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, or 100%.
[0039] In the present application, the amount of lithium removal is obtained by testing as follows: for the synthesized initial positive electrode material, first, the molar percentage content A of lithium element in the initial positive electrode material relative to the total molar amount of element T (Ni / Co / Mn) and element q is obtained by inductively coupled plasma spectrometer (ICP) testing; then the synthesized initial positive electrode material and lithium sheet are assembled into a button battery, the button battery is charged to 4.4V at a constant current of 0.1C in the voltage range of 3.0V to 4.4V, disassembled to obtain the positive electrode material, and the molar percentage content B of lithium element in the positive electrode material relative to the total molar amount of element T (Ni / Co / Mn) and element Q in the state charged to 4.4V is obtained by ICP testing. Lithium removal amount = (1-B / A) × 100%. For the positive electrode material in the full battery, the only difference is that the full battery is fully discharged first, the battery is disassembled to obtain the positive electrode material, and the molar percentage content A of lithium element in the positive electrode material relative to the total molar amount of element T (Ni / Co / Mn) and element Q is obtained by ICP testing.
[0040] The inventors of the present application have discovered that element doping in the lithium layer by synthetic means can regulate the internal oxygen defects and the distance between the lithium oxygen layers. The introduction of oxygen defects inside the material can activate the redox properties of the transition metal and greatly improve the energy density of the material. At the same time, doping the lithium layer with elements of high ionic radius increases the distance between the lithium oxygen layers, which can promote the full deintercalation of lithium ions, thereby greatly increasing the amount of lithium removed from the positive electrode material. In addition, the oxygen vacancies formed on the surface can reduce the activity of oxygen on the surface of the material, stabilize the outer oxygen ions of the material, and inhibit the release of oxygen and gas production of the positive electrode material during floating charge and high-temperature storage, thereby improving the floating charge performance and high-temperature storage performance of the electrochemical device.
[0041] In some embodiments, when the button cell is charged to 4.4V, the cathode material has a strongest oxygen release peak in the range of 100°C to 500°C in a TG-MS test at above 250°C, for example, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C. The oxygen vacancies formed inside and on the surface of the cathode material of the present application reduce the activity of oxygen in the material, and the element doping in the lithium layer inhibits the structural collapse of the material under a high delithiation state, thereby inhibiting the oxygen release of the cathode material and improving the structural stability of the cathode material under high temperature and high voltage.
[0042] In some embodiments, when the button cell is charged to 4.4V, based on the mass of 50mg of the positive electrode material, the oxygen ion flux intensity of the positive electrode material in the TG-MS test is IA / 50mg, and the temperature is T℃, wherein in the range of 100℃ to 500℃, the differential dI / dT of I relative to T is less than or equal to 3×10 -13 The cathode material of the present application can inhibit the drastic oxygen release of the material, thereby improving the structural stability of the cathode material under high temperature and high voltage.
[0043] In some embodiments, when the button cell is charged to 4.4V, based on the mass of 50mg of the positive electrode material, the heat release of the positive electrode material in the TG-DSC test is W mW / 50mg, and the temperature is T℃, wherein, in the range of 100℃ to 500℃, the differential dW / dT of W relative to T is less than or equal to 0.01, for example, it can be 0.01, 0.009, 0.008, 0.007, 0.006, 0.005, 0.004, 0.003, 0.002, 0.001 or any interval thereof. The positive electrode material of the present application can suppress the violent oxygen release and heat release of the material, and improve the structural stability of the positive electrode material at high temperature and high voltage.
[0044] In some embodiments, an electrode including the positive electrode material is assembled with a lithium sheet into a button cell. When the button cell is charged and discharged at a current of 0.1C in a voltage range of 3.0V to 4.4V, the obtained capacity-voltage differential dQ / dV curve has a first oxidation peak and a first reduction peak in the range of 4.2V to 4.4V.
[0045] In some embodiments, the peak voltage of the first oxidation peak is Vol, the peak voltage of the first reduction peak is Vrl, and |Vol-Vrl|≤0.3 V. For example, the value of |Vol-Vrl| can be 0.01 V, 0.05 V, 0.10 V, 0.15 V, 0.20 V, 0.25 V, 0.30 V or any interval thereof.
[0046] In some embodiments, the capacity-voltage differential dQ / dV curve has a second oxidation peak and a second reduction peak in the range of 3.6 V to 4.0 V, the peak voltage of the second oxidation peak is Vo2, the peak voltage of the second reduction peak is Vr2, and |Vo2-Vr2|≤0.3 V. For example, the value of |Vo2-Vr2| can be 0.01 V, 0.05 V, 0.10 V, 0.15 V, 0.20 V, 0.25 V, 0.30 V or any interval thereof.
[0047] In some embodiments, the positive electrode material includes a lithium transition metal composite oxide, which includes element T and an optional element Q, wherein the element T includes at least one of Ni, Co or Mn, and the element Q includes at least one of K, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge.
[0048] In some embodiments, based on the total molar amount of the element T, the molar percentage of Ni is 30% to 70%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or any interval thereof. In some embodiments, based on the total molar amount of the element T, the molar percentage of Mn is 0% to 70%, for example, 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or any interval thereof. In some embodiments, based on the total molar amount of the element T, the molar percentage of Co is 0% to 50%, for example, 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any interval thereof.
[0049] In some embodiments, the lithium transition metal composite oxide also includes a Na element, and based on the total molar amount of the element T and the element Q, the molar percentage of the Na element is 0.1% to 20%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 20% or any interval thereof.
[0050] In some embodiments, based on the total molar amount of the element T and the element Q, the molar percentage of the element T is 90% to 100%, for example, 90%, 91%, 94%, 96%, 98%, 99%, 100% or any interval thereof, and the molar percentage of the element Q is 0% to 10%, for example, 0%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 8%, 10% or any interval thereof.
[0051] In some embodiments, the lithium transition metal composite oxide further includes element R, and the element R includes at least one of F, Cl, Br, I or N. Based on the total molar amount of the element T and the element Q, the molar percentage of the element R is 0.1% to 10%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any interval thereof.
[0052] In some embodiments, in the lithium transition metal composite oxide, the ratio of the molar amount of Li element to the total molar amount of the element T and the element Q is 0.5 to 1.1, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1 or any range thereof.
[0053] In some embodiments, the lithium transition metal composite oxide has a layered crystal structure.
[0054] In some embodiments, the lithium transition metal composite oxide includes Li x1 Na x2 Ni y1 Mn y2 Co y3 Q z1 O 2±m R m , 0.5≤x1≤1.1, 0.001≤x2≤0.2, 0.3≤y1≤0.7, 0≤y2≤0.7, 0≤y3≤0.5, 0≤z1≤0.1, 0≤m≤0.1, wherein the element R includes at least one of F, Cl, Br, I or N.
[0055] 2. Electrochemical Device
[0056] The electrochemical device provided in the present application includes a positive electrode plate, and the positive electrode plate includes the positive electrode material described in the first aspect of the present application.
[0057] In some embodiments, the positive electrode plate also includes a conductive agent and a binder. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polytetrafluoroethylene, polyvinylidene fluoride, or vinylidene fluoride-hexafluoropropylene copolymer, etc. In some embodiments, the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers and mixtures thereof. In some embodiments, the carbon-based material is selected from carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, graphene or any combination thereof. In some embodiments, the metal-based material is selected from metal powder or metal fiber. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0058] In some embodiments, the positive electrode further comprises a positive electrode current collector. In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material on a polymer substrate.
[0059] In some embodiments, the electrochemical device further includes a negative electrode.
[0060] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of a carbon material or a silicon material. The carbon material includes at least one of graphite and hard carbon, and the silicon material includes at least one of silicon, silicon oxide, silicon carbon compound or silicon alloy. In some embodiments, the negative electrode active material layer contains a binder. In some embodiments, the binder includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polyvinyl ether or styrene-butadiene rubber. In some embodiments, the negative electrode active material layer also includes a conductive material to improve the electrode conductivity. In some embodiments, the conductive material includes at least one of conductive carbon black, acetylene black, carbon nanotubes, Ketjen black or graphene.
[0061] In some embodiments, the electrochemical device further comprises an electrolyte or a solid electrolyte.
[0062] In some embodiments, the electrolyte that can be used in the embodiments of the present application can be an electrolyte known in the prior art.
[0063] In some embodiments, the electrolyte includes an organic solvent, a lithium salt and an additive. In some embodiments, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate or ethyl propionate. In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), bistrifluoromethanesulfonyl imide lithium LiN(CF3SO2)2(LiTFSI), bis(fluorosulfonyl)imide lithium Li(N(SO2F)2)(LiFSI), lithium bis(oxalate borate) LiB(C2O4)2(LiBOB) or lithium di(oxalate borate) LiBF2(C2O4)(LiDFOB). In some embodiments, the additive includes at least one of a sulfur-oxygen double bond compound or a polynitrile compound.
[0064] In some embodiments, the sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone, vinyl sulfate, 2,4-butane sultone, 1,4-butane sultone, methylene disulfonate, 1,3-propane disulfonic anhydride, 4-methyl ethylene sulfate, or pentaerythritol bicyclic sulfate. In some embodiments, based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.1% to 5%, for example, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, or any interval thereof. In some embodiments, the polynitrile compound includes at least one of succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, sunflower dinitrile, methyl glutaronitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3,5-pentanetricarbonitrile, 1,3,6-hexanetrinitrile or 1,2,3-tris(2-cyanoethoxy)propane. In some embodiments, based on the mass of the electrolyte, the mass percentage of the polynitrile compound is 1% to 10%, for example 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0% or any interval thereof.
[0065] In some embodiments, in the electrochemical device, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the embodiments of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed by a material that is stable to the electrolyte of the present application. For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected. A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinyl pyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. The polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or a copolymer of vinylidene fluoride-hexafluoropropylene.
[0066] In some embodiments, the electrochemical device of the present application includes, but is not limited to: all kinds of primary batteries or secondary batteries. In some embodiments, the electrochemical device is a lithium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: lithium metal secondary battery, lithium ion secondary battery, lithium polymer secondary battery or lithium ion polymer secondary battery.
[0067] 3. Electronic Devices
[0068] The electronic device of the present application may be any device using the electrochemical device according to the second aspect of the present application.
[0069] In some embodiments, the electronic device includes, but is not limited to: laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries or lithium-ion capacitors, etc.
[0070] Examples and Comparative Examples
[0071] Example 1
[0072] Preparation of cathode materials
[0073] (1) preparing a mixed solution containing NiSO4 and MnSO4 according to the element molar ratio of Ni:Mn=50:50, mixing the mixed solution with a precipitant (NaOH solution) and a complexing agent (ammonia water) for reaction, controlling the reaction time to 60 hours, the ammonia concentration to 1 mol / L, and the pH to 12.2 to obtain a nickel-manganese precursor T(OH)2 (T represents Ni / Mn) having an average particle size Dv50 of 11 μm;
[0074] (2) grinding and mixing the nickel-manganese precursor and sodium carbonate in a molar ratio of (Ni+Mn) to Na of 1:1.05, calcining at 800° C. in an air atmosphere for 20 h, and then crushing, screening, and demagnetizing to obtain a first product;
[0075] (3) mixing the first product with a lithium source (a mixture of lithium hydroxide and lithium nitrate in a molar ratio of 1:1), wherein the mass ratio of the lithium source to the first product is 10:1, heating the mixture to 400° C. at a rate of 10° C. / min, maintaining the temperature for 14 hours, and cooling the mixture to room temperature in a mixture of Ar and air (volume ratio of 1:1) at a cooling rate of 50° C. / min to obtain a second product;
[0076] (4) The second product is washed, soaked and dried in deionized water, and finally crushed and sieved to obtain a positive electrode material.
[0077] Embodiment 2-10
[0078] The difference from Example 1 is that the holding time in step (3) is adjusted to 13 hours, 12 hours, 11 hours, 10 hours, 8 hours, 6 hours, 5.5 hours, 5 hours, 4 hours, and 3 hours, respectively, to regulate the content of Na element in the positive electrode material.
[0079] Button battery production
[0080] The positive electrode material, the binder polyvinylidene fluoride (PVDF), and the conductive agent conductive carbon black (Super P) in a weight ratio of 90:5:5 are mixed, added into N-methylpyrrolidone (NMP) and mixed evenly to prepare a positive electrode slurry with a solid content of 0.7; the mixed positive electrode slurry is evenly coated on an aluminum foil with a coating thickness of 40 μm and single-sided coating; after drying, the desired electrode is formed by roller pressing, wherein the electrode coating surface density is 14 mg / cm 2 The positive electrode sheet is obtained by drying and punching into 14 mm discs to obtain a single-sided positive electrode sheet; the isolation film is punched into 18 mm discs; the negative electrode used is a lithium metal sheet with a diameter of 18 mm; LiPF6 is added to a solvent mixed with propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) (PC:EC:DEC weight ratio 1:1:1) and mixed evenly to obtain an electrolyte; based on the total weight of the electrolyte, the LiPF6 The mass concentration is 12.5%; move the positive electrode sheet, isolation membrane, negative electrode sheet (lithium sheet) and electrolyte, battery shell and other accessories into the glove box (the water content must be less than 11ppm); assemble the battery in the stacking order from bottom to top and inject the electrolyte: negative electrode shell> flat pad + appropriate amount of electrolyte> metal lithium sheet + appropriate amount of electrolyte> a layer of isolation membrane + appropriate amount of electrolyte> positive electrode sheet + appropriate amount of electrolyte> flat pad + appropriate amount of electrolyte> shrapnel> positive electrode shell; package on a packaging machine to obtain a button battery.
[0081] Production of Lithium-ion Soft-Pack Batteries
[0082] Preparation of the positive electrode: Mix the positive electrode material, binder polyvinylidene fluoride (PVDF), and conductive agent conductive carbon black (Super P) in a weight ratio of 96:2:2, add them to N-methylpyrrolidone (NMP) and mix them evenly to prepare a positive electrode slurry with a solid content of 0.7; evenly coat the mixed positive electrode slurry on one side of the aluminum foil, and repeat the above steps on the other side of the aluminum foil after drying to obtain a double-sided coated positive electrode sheet; cold press, cut, and weld the pole ears to obtain the positive electrode.
[0083] Preparation of negative electrode: artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose (CMC) are mixed with deionized water in a mass ratio of 96:2:2, and stirred evenly to obtain negative electrode slurry. The negative electrode slurry is evenly coated on one side of the copper foil, and after drying, the above steps are repeated on the other side of the copper foil to obtain a double-sided coated negative electrode sheet; after cold pressing, cutting, and welding the pole ears, the negative electrode is obtained.
[0084] Preparation of electrolyte: In a dry argon environment, LiPF6 is added to a solvent mixed with propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) (PC:EC:DEC weight ratio of 1:1:1) and mixed evenly to obtain an electrolyte, wherein the mass concentration of LiPF6 based on the total weight of the electrolyte is 12.5%.
[0085] Preparation of isolation membrane: Polyethylene (PE) porous polymer film is used as the isolation membrane.
[0086] Assembly of lithium-ion soft-pack batteries: stack the positive electrode, separator, and negative electrode in order, place the separator between the positive and negative electrodes to isolate them, and wind them to obtain a bare cell. Place the bare cell in an outer packaging aluminum-plastic film, inject electrolyte, and package it. After formation, degassing, trimming and other process steps, a lithium-ion soft-pack battery is obtained.
[0087] Examples 11-25
[0088] The difference from Example 7 is that step (2) is performed as follows:
[0089] (2) The nickel-manganese precursor, sodium carbonate and element Q source (calcium hydroxide, strontium hydroxide, chromium trioxide, tungsten trioxide, molybdenum trioxide, niobium pentoxide, zirconium dioxide) are ground and mixed uniformly according to a (Ni+Mn) : Na molar ratio of 1:1.05 and Q: (Ni+Mn+Q) according to the ratio shown in Table 1, and calcined at 800°C in an air atmosphere for 20 hours, and then crushed, sieved and demagnetized to obtain a first product.
[0090] Comparative Example 1
[0091] Preparation of positive electrode material: (1) A mixed solution containing NiSO4 and MnSO4 was prepared according to the element molar ratio Ni:Mn=50:50, and the mixed solution was mixed with a precipitant (NaOH solution) and a complexing agent (ammonia water) for reaction. The reaction time was controlled to be 60 hours, the ammonia concentration was 1 mol / L, and the pH was 12.2 to obtain a nickel-manganese precursor Ni with an average particle size Dv50 of 11 μm. 0.5 Mn 0.5 (OH)2; (2) grinding and mixing the nickel manganese precursor and lithium carbonate in the above step according to the molar ratio of Li:element T (Ni / Mn) of 1.02, calcining at 800°C in an air atmosphere for 20h, cooling to room temperature at a rate of 10°C / min, and finally crushing and sieving to obtain the positive electrode material.
[0092] Comparative Example 2
[0093] Preparation of positive electrode materials: (1) A mixed solution containing NiSO4, CoSO4, and MnSO4 was prepared according to the element molar ratio of Ni: Co: Mn = 80: 10: 10, and the mixed solution was mixed with a precipitant (NaOH solution) and a complexing agent (ammonia water) for reaction. The reaction time was controlled to be 48 hours, the ammonia concentration was 1 mol / L, and the pH was 12.8 to obtain a ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2; (2) the ternary precursor and lithium hydroxide in the above steps are ground and mixed evenly according to the molar ratio of Li: element T (Ni / Co / Mn) of 1.02, calcined at 750°C in an oxygen atmosphere for 20 hours, cooled to room temperature at a rate of 10°C / min, and finally crushed and sieved to obtain the positive electrode material.
[0094] Test Method
[0095] 1. Lithium removal test
[0096] For the initial positive electrode materials synthesized in the embodiments and comparative examples, the molar percentage A of lithium element relative to the total molar amount of element T (Ni / Co / Mn) and element Q in the initial positive electrode material was obtained by inductively coupled plasma spectrometer (ICP) testing.
[0097] The pole piece containing the positive electrode material is assembled into a button battery according to the method described in the embodiment, the button battery is charged to 4.4V at a constant current of 0.1C, the positive pole piece is disassembled, the positive electrode material is scraped off, and the molar percentage content B of the lithium element in the positive electrode material relative to the total molar amount of the element T (Ni / Co / Mn) and the element Q in the state charged to 4.4V is obtained by ICP test. The amount of lithium removed = (1-B / A) × 100%.
[0098] 2. High temperature storage capacity recovery rate test
[0099] The lithium-ion soft-pack battery is charged to 4.35V at 0.7C constant current at 25°C, and then charged to 0.02C at 4.35V, so that the lithium-ion soft-pack battery reaches a fully charged state, and then discharged at 0.2C constant current to 3.0V, and the above steps are repeated twice, and the discharge capacity of the second cycle is calculated as C1; the lithium-ion soft-pack battery is fully charged according to the above steps, and placed in a 60°C constant temperature box for 60 days, and then the battery is taken out. After the battery is placed at a constant temperature of 25°C, it is cycled twice according to the above charge and discharge steps, and the discharge capacity of the second cycle is calculated as C2; high temperature storage capacity recovery rate = C2 / C1×100%.
[0100] 3. 4.45V floating charge thickness expansion rate test
[0101] The lithium-ion soft-pack battery is charged at 45°C with a constant current of 1C to 4.45V, and then charged at a constant voltage of 4.45V to a current of 0.05C. The thickness of the battery is tested and recorded with a micrometer, recorded as H0; let it stand at 45°C for 1h, charge it at a constant current of 0.4C to 4.45V, and then charge it at a constant voltage of 4.45V for 1000h. The thickness of the battery is tested and recorded with a micrometer, recorded as H1; 4.45V floating charge thickness expansion rate = (H1-H0) / H0×100%.
[0102] 4. TG-MS / DSC linkage test
[0103] The button cell was fully charged to 4.4V at a charging rate of 0.1C and then disassembled. The disassembled positive electrode was immersed in dimethyl carbonate (DMC) to remove the residual electrolyte. After natural air drying, it was transferred to the TG-MS / DSC linkage equipment and heated to 700℃ at a heating rate of 3℃ / min. The heat and oxygen signals generated in the process were collected.
[0104] The test results of button cells and lithium-ion soft-pack batteries obtained in various embodiments and comparative examples are shown in Table 1. From the comparison between Examples 1-25 and Comparative Example 1, it can be seen that the positive electrode material of the embodiment of the present application has a lithium layer doped with Na element and the material is rich in oxygen vacancies inside and on the surface, so that the dQ / dV curve of the assembled button cell has a first oxidation peak and a first reduction peak in the range of 4.2V to 4.4V, which makes the positive electrode material have a higher lithium desorption amount in the 4.4V charging state, thereby greatly improving the energy density of the lithium-ion battery. At the same time, it can be seen from the comparison of Examples 1-25 with Comparative Example 2 that the positive electrode material in the embodiment of the present application has a higher strongest oxygen release peak temperature on the basis of a higher lithium removal amount, indicating that the oxygen vacancies formed inside and on the surface of the positive electrode material of the present application reduce the activity of oxygen in the material, and the Na element doping in the lithium layer inhibits the structural collapse of the material under a high lithium removal state, thereby inhibiting the release of oxygen from the positive electrode material, and improving the structural stability of the positive electrode material at high temperature and high voltage, so that the lithium ion battery has a lower floating charge thickness expansion rate and a higher high temperature storage capacity recovery rate. In addition, the positive electrode material in the embodiment of the present application has significantly reduced dI / dT and dW / dT, indicating that the positive electrode material in the embodiment of the present application can inhibit the drastic oxygen release of the material, thereby having better structural stability at high temperature and high voltage.
[0105]
[0106]
[0107] Embodiment 26-40
[0108] The difference from Example 1 is that the electrolyte is prepared as follows: in a dry argon environment, additives are added according to Table 2 to a solvent mixed with propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) (PC:EC:DEC weight ratio of 1:1:1), and then LiPF6 is added and mixed evenly to obtain an electrolyte, wherein the contents of the additives and LiPF6 are based on the total weight of the electrolyte, and the mass concentration of LiPF6 is 12.5%.
[0109] Table 2
[0110]
[0111] From the comparison of Examples 26-40 in Table 2 with Example 1, it can be seen that by further adding sulfur-oxygen double bond compounds and / or polynitrile compounds to the electrolyte, the high-temperature storage capacity recovery rate of the lithium-ion battery can be further improved. The possible reason is that the sulfur-oxygen double bond compound can form an oxidation-resistant protective film on the surface of the positive electrode material, and the rich S element can stabilize the high-valent transition metal in the charged state, thereby better inhibiting the release of oxygen on the surface of the positive electrode material and the oxidative decomposition of the electrolyte. The polynitrile compound can complex with the transition metal on the surface of the positive electrode active material, stabilize the transition metals such as nickel, cobalt, and manganese on the surface of the positive electrode material, inhibit the release of oxygen on the surface of the positive electrode material, and thus improve the structural stability of the positive electrode material under high-temperature storage.
[0112] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. Those of ordinary skill in the art should recognize that the described embodiments may be modified and changed without departing from the spirit and principles of the present application, and these modifications and changes also fall within the scope of protection of the present application.
Claims
1. A positive electrode material, characterized in that: The electrode including the positive electrode material is assembled with a lithium sheet into a button battery. When the button battery is charged to 4.4V, the lithium removal amount of the positive electrode material is above 80%.
2. The positive electrode material according to claim 1, characterized in that When the button cell is charged to 4.4V, the strongest oxygen release peak of the positive electrode material in the range of 100°C to 500°C is above 250°C in a TG-MS test.
3. The positive electrode material according to claim 1, characterized in that When the button cell is charged to 4.4V, based on the mass of 50mg of the positive electrode material, the oxygen ion flux intensity of the positive electrode material in the TG-MS test is IA / 50mg, and the temperature is T℃, wherein in the range of 100℃ to 500℃, the differential dI / dT of I relative to T is less than or equal to 3×10 -13 .
4. The positive electrode material according to claim 1, characterized in that When the button battery is charged to 4.4V, based on the mass of 50mg of the positive electrode material, the heat released by the positive electrode material in the TG-DSC test is W mW / 50mg, and the temperature is T℃, wherein, in the range of 100℃ to 500℃, the differential dW / dT of W relative to T is less than or equal to 0.
01.
5. The positive electrode material according to claim 1, characterized in that The electrode including the positive electrode material is assembled with a lithium sheet into a button battery. When the button battery is charged and discharged at a current of 0.1C in a voltage range of 3.0V to 4.4V, the obtained capacity-voltage differential dQ / dV curve has a first oxidation peak and a first reduction peak in the range of 4.2V to 4.4V.
6. The positive electrode material according to claim 5, characterized in that The peak voltage of the first oxidation peak is Vo1, the peak voltage of the first reduction peak is Vr1, and |Vo1-Vr1|≤0.3V.
7. The positive electrode material according to claim 5, characterized in that The capacity-voltage differential dQ / dV curve has a second oxidation peak and a second reduction peak in the range of 3.6V to 4.0V, the peak voltage of the second oxidation peak is Vo2, the peak voltage of the second reduction peak is Vr2, and |Vo2-Vr2|≤0.3V.
8. The positive electrode according to claim 1, characterized in that The positive electrode material includes a lithium transition metal composite oxide, the lithium transition metal composite oxide includes an element T and an optional element Q, the element T includes at least one of Ni, Co or Mn, and the element Q includes at least one of K, Ca, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, La, Ce, Hf, Ta, W, Pb, Al, Mg, B, Si, P, S, Ti, V, Cr, Fe, Cu, Zn, Ga or Ge; the lithium transition metal composite oxide satisfies at least one of the following conditions: (1) Based on the total molar amount of the element T, the molar percentage of Ni is 30% to 70%; (2) Based on the total molar amount of the element T, the molar percentage of Mn is 0% to 70%; (3) Based on the total molar amount of the element T, the molar percentage of Co is 0% to 50%; (4) The lithium transition metal composite oxide further comprises a Na element, and the molar percentage of the Na element is 0.1% to 20% based on the total molar amount of the element T and the element Q; (5) Based on the total molar amount of the element T and the element Q, the molar percentage of the element T is 90% to 100%, and the molar percentage of the element Q is 0% to 10%; (6) The lithium transition metal composite oxide further comprises an element R, wherein the element R comprises at least one of F, Cl, Br, I or N, and the molar percentage of the element R is 0.1% to 10% based on the total molar amount of the element T and the element Q; (7) In the lithium transition metal composite oxide, the ratio of the molar amount of the Li element to the total molar amount of the element T and the element Q is 0.5 to 1.1; (8) The lithium transition metal composite oxide has a layered crystal structure; (9) The lithium transition metal composite oxide includes Li x1 Na x2 Ni y1 Mn y2 Co y3 Q z1 O 2±m R m , 0.5≤x1≤1.1, 0.001≤x2≤0.2, 0.3≤y1≤0.7, 0≤y2≤0.7, 0≤y3≤0.5, 0≤z1≤0.1, 0≤m≤0.1, wherein the element R includes at least one of F, Cl, Br, I or N.
9. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, and the positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 8.
10. The electrochemical device according to claim 9, characterized in that The electrochemical device further comprises an electrolyte, wherein the electrolyte comprises an additive, the additive comprises at least one of a sulfur-oxygen double bond-containing compound or a polynitrile compound, and the electrolyte satisfies at least one of the following conditions: (1) The sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone, vinyl sulfate, 2,4-butane sultone, 1,4-butane sultone, methylene disulfonate, 1,3-propane disulfonic anhydride, 4-methylethylene sulfate or pentaerythritol bicyclic sulfate; (2) Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.1% to 5%; (3) The polynitrile compound includes at least one of succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, scutonitrile, methyl glutaronitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3,5-pentanetricarbonitrile, 1,3,6-hexanetrinitrile or 1,2,3-tris(2-cyanoethoxy)propane; (4) Based on the mass of the electrolyte, the mass percentage of the polynitrile compound is 1% to 10%.
11. An electronic device comprising the electrochemical device according to claim 9 or 10.
Citation Information
Patent Citations
Positive electrode active material, positive electrode plate and lithium ion secondary battery
CN112447968A
Positive electrode active material, electrochemical device, and electronic device
CN115104203A
Positive electrode material, and electrochemical device and electronic device including positive electrode material
CN116325219A
Positive electrode material, electrochemical device, and electronic device
CN116802841A
Metal hydroxide, positive electrode material, electrochemical device, and electric appliance
CN116806381A
